DEVELOPING STUDENTS’ WRITING SKILLS THROUGH INSTAGRAM CAPTION ACTIVITIES: A SYSTEMATIC LITERATURE REVIEW - Melinah Diana Putri; Nabila Nabila; Naf’an Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
This paper aims to assess the effectiveness of Instagram caption activities in enhancing students’ writing skills within English as a Foreign Language (EFL) contexts from 2020 to 2025. As digital learning continues to evolve, Instagram has emerged as a widely used instructional tool that promotes authentic, multimodal, and engaging writing practices. A total of nine empirical studies published between 2020 and 2025 were systematically reviewed through databases including Google Scholar, ERIC, Mendeley, and peer-reviewed journals. The selection followed PRISMA procedures, encompassing identification, screening, eligibility assessment, and final inclusion. The findings indicate that Instagram caption activities positively impact multiple aspects of writing, including idea generation, vocabulary development, grammatical accuracy, coherence, creativity, and learner motivation. Visual prompts facilitate content creation, while the concise caption format encourages purposeful and organized writing. Furthermore, peer interaction and feedback, coupled with exposure to a real audience, enhance students’ confidence and engagement in writing tasks. However, the effectiveness of this instructional approach relies on careful pedagogical design, teacher guidance, and the integration of process-writing stages. Overall, Instagram caption activities offer an innovative, relevant, and practical strategy for developing EFL students’ writing skills, supporting both linguistic competence and 21st-century digital literacy in contemporary language classrooms.